Thyme (Thymus quinquecostatus Celak) Polyphenol-Rich Extract (TPE) Alleviates HFD-Induced Liver Injury in Mice by Inactivating the TLR4/NF-κB Signaling Pathway through the Gut–Liver Axis - Xialu Sheng; Lixia Wang; Ping Zhan; Wanying He; Honglei Tian; Jianshu Liu (Foods, 2023)
Non-alcoholic fatty liver disease (NAFLD) represents a significant and urgent global health concern. Thyme (Thymus quinquecostatus Celak) is a plant commonly used in cuisine and traditional medicine in Asian countries and possesses potential liver-protective properties. This study aimed to assess the hepatoprotective effects of thyme polyphenol-rich extract (TPE) on high-fat diet (HFD)-induced NAFLD and further explore possible mechanisms based on the gut–liver axis. HFD-induced liver injury in C57 mice is markedly ameliorated by TPE supplementation in a dose-dependent manner. TPE also regulates the expression of liver lipid metabolic genes (i.e., Hmgcr, Srebp-1, Fasn, and Cyp7a1), enhancing the production of SCFAs and regulating serum metabolites by modulating gut microbial dysbiosis. Furthermore, TPE enhances the intestinal barrier function and alleviates intestinal inflammation by upregulating tight junction protein expression (i.e., ZO-1 and occluding) and inactivating the intestinal TLR4/NF-κB pathway in HFD-fed mice. Consequently, gut-derived LPS translocation to the circulation was blocked, the liver TLR4/NF-κB signaling pathway was repressed, and subsequent pro-inflammatory cytokine production was restrained. Conclusively, TPE might exert anti-NAFLD effects through the gut–liver axis and has the potential to be used as a dietary supplement for the management of NAFLD.